Incidence of Anemia in Pregnant Women with Closer Spacing of Pregnancies and Multiparity: A Case Report - Lia Nur Amalina (HM Publisher, 2023)
Background: One of the risk factors that can increase the incidence of anemia in pregnant women is the close spacing of pregnancies and multiparity. Closely spaced pregnancies refer to pregnancies that occur within a short time after the previous birth, while multiparity refers to a woman who has given birth to more than one child previously. The combination of these two factors can lead to an increased risk of anemia in pregnant women. This study presents the risk of closely spaced pregnancies and multiparity for the incidence of anemia in pregnant women. Case presentation: Mrs. SM, 27 years old pregnant woman, came with complaints of severe dizziness for the last 2 weeks. In addition, patients also complain of weakness, weakness, no energy, and no appetite. The patient said that she was currently pregnant with her 4th child, aged 27-28 weeks, with active fetal movements. Hemoglobin examination 7 mg/dL. Conclusion: The patient was diagnosed with anemia in pregnant women with risk factors for close pregnancy spacing and multiparity.